The Relationship between Big Five Personality Traits of School Administrators with Managerial Resourcefulness - Karabatak, Songul (Hacettepe Univ, 2021)
In this study, the relationship between managerial resourcefulness and personality traits of school administrators was examined. Relational research model was used in the study. The sample was determined by the method of disproportionate stratified sampling. In the analysis of the data collected with the Ten-Item Personality Scale and the Managerial Strength Scale, descriptive statistics, correlation, and regression analysis were used. At the end of the study, school administrators' managerial resourcefulness was found at the medium level. School administrators indicated that they were mostly task-oriented and had conscientiousness personality trait. It was revealed that while there was a positive and meaningful relationship between both managerial resourcefulness and its dimensions and openness to experience personality trait, there wasn't any relation between managerial resourcefulness and other four personality traits. In addition, the more perseverance and task-focused administrators were more conscientious. An big five personality traits had a low level and meaningful relationship to managerial resourcefulness of administrators. It was also seen that only openness to experience is a significant predictor of managerial resourcefulness, while other personality traits have no significant effect on managerial resourcefulness. Finally, some suggestions were made according to the results of the study.
Okul yöneticilerinin beş faktör kişilik özellikleri ile yönetsel güçlülükleri arasındaki ilişki
Keywords: Big five personality theory; personality; managerial resourcefulness; school administrator